"You're more engaged when you're listening to somebody tell their story": A qualitative exploration into the mechanisms of the podcast 'menopause: unmuted' for communicating health information. Issue 12 (December 2022) - Shaw, Philippa A.; Sumner, Amy L.; Halton, Candida C.; Bailey, Stacy C.; Wolf, Michael S.; Andrews, Emma N.; Cartwright, Tina
Abstract: Objective: While health podcasts can be effective in reducing stigma and increasing knowledge, we know little about their mechanisms of action. This qualitative study explored the mechanisms of how women connected with the podcast 'menopause: unmuted', which presented menopause information in a storytelling format. Methods: A diverse sample of 30 women aged 40–60 years were interviewed after listening to the podcast. Interviews covered participant's views and perceptions of the stories presented. Transcripts were analyzed thematically. Findings: Two overarching themes were identified. 'Openness and authenticity' describes the value of personal stories told in an authentic way by real experts-by-experience. 'Relatability and representation' explores participants' emotional reaction to the podcast, influenced by the extent to which they identified with the stories and storytellers on the podcast. Conclusions: Authenticity and relatability were identified as key mechanisms through which participants connected with audio stories, consistent with Fisher's narrative theory. These findings have important implications for the application of storytelling in podcasts designed to influence health behaviors. Practice implications: Diverse stories representing a range of demographic characteristics and experiences are needed when creating podcasts about health information to increase listener's relatability and connection. Highlights: Story-based podcasts are an engaging and effective way to learn about menopause. Content is seen as authentic, credible and may influence health behaviours. Connection and impact depend on relatability, aligned to Fisher's narrative theory. Podcasts should seek to enhance engagement through representing diverse audiences.